Cardiac ventricular sizes are reduced in patients with long-term, normoalbuminuric type 1 diabetes compared to the non-diabetic background population. (May 2019) - Hjortkjær, Henrik Ø; Jensen, Tonny; Hilsted, Jannik; Mogensen, Ulrik M; Corinth, Helle; Rossing, Peter; Sigvardsen, Per E; Fuchs, Andreas; Kühl, J Tobias; Nordestgaard, Børge G; Køber, Lars; Kofoed, Klaus F
Aims: Type 1 diabetes entails increased cardiovascular morbidity and cardiac chamber sizes are associated with cardiovascular disease. The aim of this study was to compare cardiac chamber sizes in normoalbuminuric persons with type 1 diabetes to a background population without diabetes. Methods: In a cross-sectional study, we examined 71 normoalbuminuric persons with long-term type 1 diabetes without known cardiovascular disease using cardiac multi-detector computed tomography. Cardiac chamber sizes and left ventricular remodelling were compared to persons without diabetes from the Copenhagen General Population Study. Results: Participants were median (interquartile range) 54 (48–60) (type 1 diabetes) and 57 (50–64) (without diabetes) years old and 59% were men (both groups). Participants with type 1 diabetes had smaller left ventricular mass (−3.5 g/m 2, 95% confidence interval −5.8 to −1.3) and left (−4.0 mL/m 2, 95% confidence interval −6.9 to −1.0) and right (−11.7 mL/m 2, 95% confidence interval −15.4 to −7.9) ventricular volumes in multivariable analyses (adjusted for age, sex, body composition, blood pressure and antihypertensive medication), but no differences in atrial volumes. Conclusion: Persons with long-term type 1 diabetes had smaller left ventricular mass and biventricular volumes, yet similar atrial sizes, compared to a background population without diabetes. These findings may reflect subclinical development of diabetic cardiomyopathy.